Fungal and mycotoxin contamination in mixed feeds: evaluating risk in cattle intensive rearing operations (Feedlots) - Gonzalez Pereyra, Maria Laura (2013)
Argentina is the fourth global beef producer. Exposure to mycotoxins through contaminated feed is a major hazard for ruminants. In the present study we assess mycobiota, aflatoxin B1 (AFB1 ), fumonisin B1 (FB1 ), deoxynivalenol (DON) and zearalenone (ZEA) levels in total mixed rations (TMRs) during two consecutive years. Total fungal counts were evaluated and fungal species were identified. Also, ability of A. flavus isolates to produce AFB1 in vitro was tested. Natural contamination with AFB1 and FB1 was quantified by HPLC. Deoxynivalenol and zearalenone were analysed by immunochromatography and TLC, respectively. Fungal counts varied from ND to 2.10 x 108 CFU/g. The prevalent genera were Aspergillus spp. (60%) and Fusarium spp. (66.7%), respectively. The prevalent species was Aspergillus fumigatus. Fifty percent of A. flavus strains produced 75 to 112.5 µg/g AFB1 . Forty- six percent of 2007 samples were contaminated with 4 to 10 µg/ kg AFB1 . Deoxynivalenol was detected in 33.3 % of the samples (≥ 1. 25 µg/g). Fumonisin B1 and ZEA were not detected. This study can be useful to estimate the mycotoxicological risk of cattle TMRs in this region and to compare results with studies from other beef-producing countries.